The 2015-19 multi year drought in the Eastern Cape, South Africa: it's evolution and impacts on agriculture. (January 2022) - Archer, Emma; du Toit, Justin; Engelbrecht, Christien; Hoffman, M. Timm; Landman, Willem; Malherbe, Johan; Stern, Maryke
Abstract: The Eastern Cape Province, and in particular, it's interior western Karoo region, has long been subject to periodic droughts, with significant implications for it's agricultural sector. From 2015, with some recovery in 2020, the area experienced a severe multi year drought, with negative impacts for a range of sectors, including extensive livestock farming. At the time of the drought, a common narrative in the media stated that the drought was unprecedented. In this paper, we analyze how the drought evolved climatically, as well as its impacts on vegetation and farming conditions. Our findings indicate that it would appear that the drought was not unprecedented. It was, however, considered to be extremely severe – with some local impacts found to be critical. Loss of production impacts, and loss of income, now compounded by the difficulties resulting from the COVID19 pandemic (which has impacted the South African economy severely) are likely to continue to impact the agricultural sector in the Eastern Cape for some time – and given the likelihood of increased frequency of extreme events in southern Africa in the future, we may see more frequent subsequent severe multi-year events. Highlights: From 2015, the interior Eastern Cape experienced a severe multi year drought Popular media narratives described the drought as unprecedented. In fact, the drought was not unprecedented, but was extremely severe. The agricultural sector in the Eastern Cape is likely to continue to be vulnerable.